The Influence of Product Features and Customer Satisfaction on Electronic Word of Mouth (E-WOM) with Brand Trust as a Mediating Variable among Honda Honda Vario Users in Special Region of Yogyakarta - Krisnadi, Yehizkia Putra; Heriputranto, Lukas Agung; Kaloeti, Ade Kristianus (EQUILIBRIUM - Jurnal Bisnis dan Akuntansi, 2026)
This study aims to analyze the influence of product features and customer satisfaction on Electronic Word of Mouth (E-WOM), with brand trust as a mediating variable among Honda Honda Vario users in the Special Region of Yogyakarta. The growing use of automatic motorcycles in urban areas requires manufacturers to continuously improve product features and maintain customer satisfaction in order to generate organic digital promotion through social media. This research employed a quantitative approach using a survey method involving 250 Honda Honda Vario users in the Special Region of Yogyakarta. The sampling technique used was purposive sampling. Data were analyzed using Structural Equation Modeling based on Partial Least Squares (SEM-PLS). The results indicate that product features have a positive effect on customer satisfaction. Customer satisfaction positively affects brand trust. Brand trust has a significant effect on E-WOM. Product features also have a direct effect on E-WOM. Furthermore, brand trust is proven to mediate the relationship between customer satisfaction and E-WOM. These findings emphasize the importance of feature innovation and strengthening brand trust in encouraging consumer advocacy in the digital era.